Pemberdayaan Kader Kesehatan dalam Pencegahan Stunting di Desa Tenggelang - Nurfadhila Nurfadhila; Nur Isriani Najamuddin; Zaenal Abidin (Yayasan Inspirasi El Burhani, 2023)
Introduction: Stunting is a condition where a child's physical growth and development is hampered due to a lack of adequate nutrition, especially during the period from pregnancy to 2 years of age and is a nutritional problem for quite a long time due to the provision of food that does not meet nutritional needs. Objective: The aim of this community service activity is to increase knowledge and motivation in efforts to prevent stunting in children through empowering health cadres in Tenggelang Village. Method: This activity takes the form of empowering health cadres in preventing stunting in children in Tenggelang Village which was held on Wednesday 06 September 2023 WITA in the Village Hall, Tenggelang Village Hall. This activity was attended by 15 health cadres and local BKKBN employees. Result: Community service activities by empowering cadres in preventing stunting in Tenggelang Village were attended by 15 participants. From the results of the pre-test analysis, some cadres already knew the role and importance of stunting prevention, but after providing material and empowering cadres, it showed that all cadres understood the role and duties of posyandu cadres, orientation for posyandu cadres, as well as material on stunting prevention in the form of the First 1000 Days of Life ( HPK). Conclusion: This activity received good feedback from health cadres with the results showing that the cadres' knowledge and motivation increased after being given the material. This community service activity can be carried out periodically so that there are no incidents of stunting in children.